Physical Adsorption and Photocatalytic Activity of Titanium Dioxide Nanotube and Graphene Oxide Composite - Tho, Nguyen Huu; Thy, Tran Thi Mai; Dat, Phan Tan; Minh, Vo Cao; Sang, Nguyen Xuan (VNU Journal of Science: Natural Sciences and Technology, 2018)
This study synthesizes graphene oxide (GO) by modified low temperature Hummer’s method and in-situ hydrothermally grown TiO 2 nanotube (TNT) on GO sheet. Transmission electron microscopic (TEM) images show the homogeneous formation of TNT with the mean diameter of ~8 nm and the co-existence of TNT and GO in the composite sample. X-ray diffraction pattern of GO indicates the successful fabrication. The UV-vis measurement with methylene blue indicates the improvement of physical adsorption and photocatalytic activity of the composite samples. Keywords TNTs, GO, physical adsorption, photocatalyst References [1] C. Dette et al., “TiO¬2 Anatase with a Bandgap in the Visible Region,” Nano Lett., vol. 14, no. 11, pp. 6533–6538, 2014. [2] A. Ibhadon and P. Fitzpatrick, “Heterogeneous Photocatalysis: Recent Advances and Applications,” Catalysts, vol. 3, no. 1, pp. 189–218, 2013. [3] Y. T. Liang, B. K. Vijayan, K. A. Gray, and M. C. Hersam, “Minimizing graphene defects enhances titania nanocomposite-based photocatalytic reduction of CO2 for improved solar fuel production,” Nano Letters, vol. 11, no. 7. pp. 2865–2870, 2011. [4] C. L. Wong, Y. N. Tan, and A. R. Mohamed, “A review on the formation of titania nanotube photocatalysts by hydrothermal treatment,” Journal of Environmental Management, vol. 92, no. 7. pp. 1669–1680, 2011. [5] Z. Bo et al., “Synthesis and stabilization of small Pt nanoparticles on TiO2partially masked by SiO2,” Appl. Catal. A Gen., vol. 551, pp. 122–128, 2018. [6] K. Bubacz, B. Tryba, and A. W. Morawski, “The role of adsorption in decomposition of dyes on TiO 2 and N-modified TiO 2 photocatalysts under UV and visible light irradiations,” Materials Research Bulletin, vol. 47, no. 11. pp. 3697–3703, 2012. [7] M. Faraji and N. Mohaghegh, “Ag/TiO2-nanotube plates coated with reduced graphene oxide as photocatalysts,” Surf. Coatings Technol., vol. 288, pp. 144–150, 2016. [8] L. C. Sim, and K. H. Leong, “Graphene oxide and Ag engulfed TiO2 nanotube arrays for enhanced electron mobility and visiblelight-driven photocatalytic performance,” Journal of Materials Chemistry A, vol. 2, no. 15. pp. 5315–5322, 2014. [9] C.-Y. Tsai, C.-W. Liu, C. Fan, H.-C. Hsi, and T.-Y. Chang, “Synthesis of a SnO 2 /TNT Heterojunction Nanocomposite as a High-Performance Photocatalyst,” J. Phys. Chem. C, vol. 121, no. 11, pp. 6050–6059, 2017. [10] S. Gayathri, M. Kottaisamy, and V. Ramakrishnan, “Facile microwave-assisted synthesis of titanium dioxide decorated graphene nanocomposite for photodegradation of organic dyes,” AIP Adv., vol. 5, no. 12, 2015. [11] H. Tao, X. Liang, Q. Zhang, and C. T. Chang, “Enhanced photoactivity of graphene/titanium dioxide nanotubes for removal of Acetaminophen,” Appl. Surf. Sci., vol. 324, pp. 258–264, 2015. [12] M.Z. Wang , F. X. Liang , B. Nie , L.H. Zeng , L. X. Zheng , Peng Lv , Y. Q. Yu , C. Xie, Y. Y. Li, “TiO2 Nanotube Array/Monolayer Graphene Film Schottky Junction Ultraviolet Light Photodetectors." Part. Part. Character. Syst., vol. 30, 7, pp. 630-636, 2013. [13] J. Yu, T. Ma, and S. Liu, “Enhanced photocatalytic activity of mesoporous TiO 2 aggregates by embedding carbon nanotubes as electron-transfer channel,” Phys. Chem. Chem. Phys., vol. 13, no. 8, pp. 3491–3501, 2011. [14] H. L. Poh, F. Šaněk, A. Ambrosi, G. Zhao, Z. Sofer, and M. Pumera, “Graphenes prepared by Staudenmaier, Hofmann and Hummers methods with consequent thermal exfoliation exhibit very different electrochemical properties,” Nanoscale, vol. 4, no. 11, p. 3515, 2012. [15] P. B. Arthi G and L. BD, “A Simple Approach to Stepwise Synthesis of Graphene Oxide Nanomaterial,” J. Nanomed. Nanotechnol., vol. 06, no. 01, 2015. [16] M. Faraldos and A. Bahamonde, “Environmental applications of titania-graphene photocatalysts,” Catal. Today, vol. 285, pp. 13–28, 2017.